2019
DOI: 10.3747/co.26.4563
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care for Cancer Patients Near End of Life in Acute-Care Hospitals across Canada: A Look at the Inpatient Palliative Care Code

Abstract: Hospitals play an important role in the care of patients with advanced cancer: nearly half of all cancer deaths occur in acute-care settings. The need for increasing access to palliative care and related support services for patients with cancer in acute-care hospitals is therefore growing. Here, we examine how often and how early in their illness patients with cancer might be receiving palliative care services in the 2 years before their death in an acute-care hospital in Canada. The palliative care code from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…In response to factors which impeded optimal EOL care, nurses gave the highest ranking of being "too busy" in both nurses and doctors. Similar findings have also been reported as an important barrier to providing quality EOL care in Thailand (Mesukko, 2010), Canada (Tung et al, 2019), Australia (Raymond, Lee, & Bloomer, 2017) and a recent explanatory systematic review (Lund et…”
Section: Notesupporting
confidence: 83%
See 1 more Smart Citation
“…In response to factors which impeded optimal EOL care, nurses gave the highest ranking of being "too busy" in both nurses and doctors. Similar findings have also been reported as an important barrier to providing quality EOL care in Thailand (Mesukko, 2010), Canada (Tung et al, 2019), Australia (Raymond, Lee, & Bloomer, 2017) and a recent explanatory systematic review (Lund et…”
Section: Notesupporting
confidence: 83%
“…Canada (Tung et al, 2019), Australia (Raymond, Lee, & Bloomer, 2017) and a recent explanatory systematic review (Lund et al,…”
Section: Ta B L E 2 (Continued)mentioning
confidence: 99%
“…The majority of expected deaths in high income countries occur in hospitals, [1][2][3][4][5][6][7] where optimal palliative care cannot be assured. 6,[8][9][10][11][12] People with palliative care needs are also often hospitalised within the last year of life, even if they don't die in this setting, [13][14][15][16] so hospital clinicians provide care intermittently to this population from diagnosis through to death.…”
Section: Introductionmentioning
confidence: 99%
“…Another Canadian study looking at inpatient palliative care code that identified patients who received or were referred to palliative care revealed that 76.8% of patients were only first identified as "palliative" in their final admission before death; for other patients receiving the designation before their final admission, nearly half were identified less than 2 months before death. 24 Some participants in our study also cautioned that a gradual normalization of MAiD discus sions, even if wellintended to promote patients' autonomy, may inadvertently move palliative care from being compassiondriven to process driven. 25 This can have important social and practice implications, as a wholeperson focus on patient emotions and suffering in their wider sociorelational context may allow HCPs to probe and clarify patient motivations, potential miscon ceptions, and needs, thereby providing tailored education and support.…”
Section: Main Findingsmentioning
confidence: 81%
“…Another Canadian study looking at inpatient palliative care code that identified patients who received or were referred to palliative care revealed that 76.8% of patients were only first identified as “palliative” in their final admission before death; for other patients receiving the designation before their final admission, nearly half were identified less than 2 months before death. 24 …”
Section: Discussionmentioning
confidence: 99%